Analisis Kesalahan Kemampuan Representasi Matematis dalam mengerjakan Soal Matematika Materi Statistik - Nia Puspita; Caswita Caswita; Agung Putra Wijaya (Mandalika Mathematics and Educations Journal, 2025)
Mathematical representation ability is the competence to present mathematical ideas in symbolic, visual, or verbal forms. This descriptive qualitative research aims to analyze students' errors in solving statistics problems based on mathematical representation ability, conducted through a literature study. The results indicate that students still have difficulty representing mathematical ideas (symbolic, visual, verbal). Key errors include conceptual errors (selecting formulas), inaccuracy in charts/diagrams, and inability to connect the data context with its representation. The contributing factors are the lack of conceptual understanding and a focus on procedures. This finding is expected to serve as a reference for teachers to strengthen students' mathematical representation ability, particularly in statistics material.